Elevated pulsatility index of the superior mesenteric artery indicated prolonged mechanical ventilation in patients after cardiac valve surgery - Zhou, Yuankai; He, Huaiwu; Cui, Na; Wang, Xiaoting; Long, Yun; Liu, Dawei (Frontiers in Surgery, 2023)
Purpose: This study examined whether alterations in Doppler parameters of superior mesenteric artery (SMA) are associated with prolonged mechanical ventilation (PMV) in patients who underwent cardiac valve surgery. Methods: Hemodynamic and SMA Doppler parameters were collected at intensive care unit(ICU) admission. The duration of mechanical ventilation was monitored. PMV was defined as mechanical ventilation ≥96 h. Results: A total of 132 patients admitted to ICU after cardiac valve surgery were evaluated for enrollment, of whom 105 were included. Patients were assigned to the control (n = 63) and PMV (n = 42) groups according to the mechanical ventilation duration. The pulsatility index(SMA-PI) and resistive index of SMA (SMA-RI) were 3.97 ± 0.77 and 0.88 (0.84–0.90) in the PMV group after cardiac valve surgery, which was lower than the SMA-PI (2.95 ± 0.71, p <0.0001) and SMA-RI of controls (0.8, 0.77-0.88, p <0.0001). SMA-PI at admission had favorable prognostic significance for PMV (AUC = 0.837, p <0.0001). Conclusions: An elevated SMA-PI is common in patients after cardiac valve surgery with PMV. Increased SMA-PI could help predict PMV after cardiac valve surgery. Using point-of-care ultrasound to measure SMA-PI at ICU admission is an acceptable and reproducible method for identifying patients with PMV.